Correlation of oxygen consumption with growth and red pigment production of Monascus purpureus in solid state fermentation of rice - Teerin Chysirichote; Prueksuda Sakoolkaew; Worasaung Klinthong (My University, 2024)
Since aeration has a crucial role in mass and heat transfer during solid-state fermentation (SSF), the aim of the present work was to find out how it related to biomass and red pigment production of Monascus purpureus TISTR3615 during SSF. The fungal consumption of oxygen, one of the air's constituents important for fungal metabolism, was used to explain the relationship between the aeration rate, the fungal growth, and the red pigment production during the SSF of rice. Findings showed that at increased aeration rates, the fungus absorbed more oxygen, which boosted fungal growth but decreased red pigment production. Conversely, red pigment production increased when the fungus' oxygen consumption decreased. Regression equations with an acceptable R2 were used to explain the relationship between M. purpureus' red pigment production and its oxygen consumption and aeration rate. The ideal oxygen concentration for increasing M. purpureus' capacity to produce red pigment was 0.0685 mmol/day/g of dry biomass, which produced red pigment at around 2,897 AU500nm/g of dry biomass. However, the optimal oxygen consumption of the fungus for overall red pigment production (including growth impact) was 1.390 mmol/day/g of dry biomass, which produced red pigment at around 2,787 AU500nm/g of dry fermented rice. The results of the present work could potentially be utilised in developing M. purpureus' red pigment production approach.
Keywords: Monascus purpureus; Solid-State Fermentation; Red rice; Red yeast rice; Microbial Metabolism and Applications